Neuro-Kinesthetic Stimulation: Optimizing Playdough Manipulation to Address Fine Motor Stagnation in 4–5-Year-Olds - Suharti; Mallevi Agustin Ningrum; Dhian Gowinda Luh Safitri; Kartika Rinakit Adhe; Budi Purwoko; Ziyadatul Ilmiyah (Universitas Pendidikan Mandalika, 2026)
This study aims to evaluate the effectiveness of optimizing playdough-based activities to enhance fine motor skills in children aged 4–5 years. Employing a quasi-experimental non-equivalent control group design, the research involved 28 children divided into an experimental group (, structured playdough intervention) and a control group (, conventional paper-based media). Data were collected using structured observation scales and performance rubrics, and analyzed via descriptive statistics, N-Gain scores, and independent t-tests. Results indicate a significant disparity in motor skill acquisition between the groups (). The experimental group’s post-test score significantly increased to 82.50 (from 56.56), yielding an N-Gain of 60.33% (Moderately Effective). Conversely, the control group only achieved an N-Gain of 24.18% (Ineffective). These findings demonstrate that the tactile resistance of playdough provides superior stimulation for the hand’s intrinsic muscles compared to traditional methods. Consequently, early childhood educators should integrate structured playdough activities into the core curriculum rather than treating them as elective play. Future research should implement longitudinal tracking to determine the long-term impact of these motor gains on formal writing readiness.